Incidence and mortality trends of nasopharynx cancer from 1990 to 2019 in China: an age-period-cohort analysis - Ruhai Bai; Jianzhong Sun; Yan Xu; Zhonghe Sun; Xiaoyan Zhao (BMC, 2022)
Abstract Background Nasopharynx cancer (NPC) is a great health burden in China. This study explored the long-term trends of NPC incidence and mortality in China. Methods We retrospectively analyzed data from the Global Burden of Disease Study 2019 using an age-period-cohort framework. Results The age-standardized incidence rate (ASIR) of NPC increased by 72.7% and age-standardized mortality rate (ASMR) of NPC decreased by 51.7% for both sexes between 1990 and 2019. For males, the local drift for incidence was higher than 0 (P < 0.05) in those aged 20 to 79 years. For females, the local drift was higher than 0 (P < 0.05) in those aged 30 to 59 years, and lower than 0 (P < 0.05) in those aged 65 to 84 years. The local drift for mortality rates were less than 0 (P < 0.05) in every age group for both sexes. The estimated period relative risks (RRs) for incidence of NPC were increased monotonically for males, and increased for females after 2000. The increasing trend of cohort RRs of incidence was ceased in recent birth cohorts. Both period and cohort effects of NPC mortality in China decreased monotonically. Conclusions Over the last three decades, the ASMR and crude mortality rate (CMR) of NPC has decreased, but the ASIR and crude incidence rate (CIR) increased in China. Although the potential mortality risk of NPC decreased, the risk of NPC incidence was found to increase as the period move forward, and suggested that control and prevention efforts should be enhanced.